Threat of Artificial Intelligence to the higher education services: statistical analyses in selected Eastern European countries - Okulicz-Kozaryn Walery; Korneliuk Bohdan; Kupczyk Teresa; Kalaman Olga; Jasinowski Aleksander; Artyukhov Artem; Artyukhova Nadiia; Malovychko Andriy; Volk Iurii (2023)
The rapid development and adoption of Artificial Intelligence (AI) is sparking numerous discussions about the pros and threats of AI technologies. Businessmen and entrepreneurs are beginning to increasingly use AI in healthcare, marketing, hospitality, science, art and education. In turn, lawyers, science fiction authors, academics, and select AI consumer groups are urging more and more caution. AI has also entered the practices of higher education. The purpose of the publication is to provide new scientific data that can serve as a basis for evidence-based planning and forecasting, as well as for multi-level management decisions. The main hypothesis of the study is the following: there are no students who think “Artificial Intelligence is a threat to the higher education services in the nearest 5 years”. The hypotheses of the study were transformed into a pair of statistical hypotheses: the Research hypothesis and the Alternative one. The authors adopted the Customer Service Theory as the theoretical basis of the study. Therefore, they surveyed 1744 consumers of educational services (students) from 8 universities in 5 Eastern European countries. The authors used reliable standard research methods. These are literature review, questionnaire survey of respondents using cloud technologies and AI tools, graphical representation of the results and statistical analysis. The primary processing and graphical representation of the survey results showed that 23.05% of the total number of respondents thinks that AI is a threat to the higher education in the nearest 5 years. Further, the authors investigated separately the opinions of students for each group of respondents. Verification of statistical hypotheses resulted in rejection of the research hypothesis for all groups of respondents. The alternative hypothesis was accepted for each group of respondents: the number of students who think Artificial Intelligence is a threat to the higher education in the nearest 5 years is greater than zero, if random variations are not taken into account. The alternative hypothesis is accepted with a high significance level of 0.01. This means that university governments and managers can make plans and forecasts, and make multi-level management decisions based on new scientific evidence. These plans, forecasts and management decisions will be made with accurate, predictable probability. The purpose of the following study is to explore in detail the threats that students see in the application of AI in higher education.